(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the mean duration of analgesia of intraperitoneal bupivacaine, ropivacaine and placebo after laparoscopic cholecystectomy. Study Design: Randomized controlled trial study. Place and Duration of Study: This study was conducted at the department of Surgery, Services Hospital, Lahore from 27th of July 2021 to 26th of January 2022. Methods: A total of 90 patients above the age of 18 years, undergoing laparoscopic cholecystectomy were included in this study and divided in to 3 equal groups, Group R (Ropivacaine group), Group B (Bupivacaine group) and Group S (Normal saline group) using computer generated randomization. Patients in Group R were administrated 35 ml of 0.375% ropivacaine (131.25 mg), patients in Group B were administrated 35 ml of 0.25% bupivacaine (87.5 mg) while patients in Group S were administrated 35 ml of 0.9% normal saline. The primary outcome was set as the significance of difference in mean duration of analgesia between the groups in the post-operative period. Results: The Mean±SD of age in this study was 40.71±12.23 years with an age range of 20 to 62 years. The ratio of male gender was higher (71.11%) compared to female gender (28.88%) in overall study population. The overall mean duration of surgery was 31.83±6.13 hours. The results of primary outcome of the study show that mean duration of analgesia in post-operative period was significantly longer in Group R compared to Group B and Group S (13.43±2.04, 7.56±1.81 and 4.13±1.1 respectively, p=0.000). Conclusion: Intraperitoneal ropivacaine provides longer duration of analgesia compared to bupivacaine and placebo after laparoscopic cholecystectomy.